Napoli-type' salami processing from various, indigenous genetics lines of pigs. III. Chemical-physical and microbiological characteristics - Diaferia C.; La Pietra L.; Longo M.; Magliano V.; Pirone G.; Rocco M. (Tradition and innovation in Mediterranean pig production, 2000)
Salami processing suitability of pork meat belonging to various native genetic lines: Calabrese (CA), Siciliana (SI), Cinta Casaldianni (CC), Cinta Senese (CS) was evaluated. Salami were dried and seasoned in cells with controlled temperature and humidity. Chemical, physical-chemical and microbiological analyses were performed. The request and usual growing of LAB during drying and its persistence at high number during seasoning, was observed. Enterobacteriaceae level reduced during all processing period. Aw values lowering was continue and homogeneous; pH values, in most cases, lowered in drying and subsequently increased. The analytical results show that these kinds of meat are quite qualified to salami processing.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)